Exploring the Adequacy of South African Water Law in Managing Non-revenue Water: A Focus on South African Cities - Steyn, Nicolene Renske (Southern African Public Law, 2022)
South African cities face significant levels of water wastage and inefficient use, which hamper the supply of water services to communities. A primary reason for this is high levels of non-revenue water, also known as water losses. Non-revenue water includes all water lost through physical leakages, commercial losses and unbilled authorised use before it reaches the consumer. Non-revenue water is estimated at more than thirty-seven per cent on average in South African cities, and up to sixty per cent in many irrigation and municipal supply schemes. For cities to increase their water supply and to provide sufficient water to communities, they must drastically decrease non-revenue water to reconcile water withdrawals with supply. This article critically examines the country’s water laws and policies to determine the specific duties that cities have with regard to the challenge of non-revenue water. The article also seeks to determine the adequacy of the law in managing non-revenue water in cities. While it finds that the law provides adequately for the regulation of non-revenue water in cities, many duties overlap and the legal framework is fragmented. The author offers several recommendations, including the development of improved oversight measures to ensure that cities fulfil the duties expected of them.